(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The research aims to evaluate the impact of the transition from local accounting standards to International Financial Reporting Standards (IFRS) on auditing procedures. For the purpose of achieving the research objective, financial statements were prepared for the research sample banks before adoption for the period (2013-2015) and after adoption for the period (2016-2019). Then the audit procedures were explained through comparison to find out the new procedures in light of the adoption. Many conclusions were reached, the most important of which is that the adoption of international accounting and financial reporting standards contributes to improving the audit procedures in the banks, the research sample, due to the complexity of bank operations and the multiplicity of its activities, as well as the areas that the IFRS9 financial reporting standard deals with. Especially in the field of evaluating financial assets and determining expected credit losses, many recommendations have been reached, the most important of which is for external audit companies and offices to improve approved audit procedures, respond quickly to requirements, and benefit from the guidelines set by international auditing standards, in particular auditing estimates and fair value.